Functional Inactivation of the Genome-Wide Association Study Obesity Gene Neuronal Growth Regulator 1 in Mice Causes a Body Mass Phenotype - Lee, Angela W.S.; Berriel Diaz, Mauricio; Herzig, Stephan (PLOS ONE, 2012)
To date, genome-wide association studies (GWAS) have identified at least 32 novel loci for obesity and body mass-related traits. However, the causal genetic variant and molecular mechanisms of specific susceptibility genes in relation to obesity are yet to be fully confirmed and characterised. Here, we examined whether the candidate gene NEGR1 encoding the neuronal growth regulator 1, also termed neurotractin or Kilon, accounts for the obesity association. To characterise the function of NEGR1 for body weight control in vivo, we generated two novel mutant mouse lines, including a constitutive NEGR1-deficient mouse line as well as an ENU-mutagenised line carrying a loss-of-function mutation (Negr1-I87N) and performed metabolic phenotypic analyses. Ablation of NEGR1 results in a small but steady reduction of body mass in both mutant lines, accompanied with a small reduction in body length in the Negr1-I87N mutants. Magnetic resonance scanning reveals that the reduction of body mass in Negr1-I87N mice is due to a reduced proportion of lean mass. Negr1-I87N mutants display reduced food intake and physical activity while normalised energy expenditure remains unchanged. Expression analyses confirmed the brain-specific distribution of NEGR1 including strong expression in the hypothalamus. In vitro assays show that NEGR1 promotes cell-cell adhesion and neurite growth of hypothalamic neurons. Our results indicate a role of NEGR1 in the control of body weight and food intake. This study provides evidence that supports the link of the GWAS candidate gene NEGR1 with body weight control.
Gesehen am 27.04.2018